Stroke in Athletes with Atrial Fibrillation: A Narrative Review - Joana Certo Pereira; Maria Rita Lima; Francisco Moscoso Costa; Daniel A. Gomes; Sérgio Maltês; Gonçalo Cunha; Hélder Dores; Pedro Adragão (Diagnostics)
Atrial fibrillation (AF) is the most common sustained arrhythmia, linked with a significantly heightened risk of stroke. While moderate exercise reduces AF risk, high-level endurance athletes paradoxically exhibit a higher incidence. However, their stroke risk remains uncertain due to their younger age, higher cardiovascular fitness, and lower rate of comorbidities. Several key studies highlight that AF may increase the risk of stroke in endurance athletes, particularly those over 65. However, the overall risk within this population remains relatively low. Notably, older male athletes show a higher AF incidence but experience lower stroke risk than their non-athletic counterparts. Regular physical activity prior to a first stroke appears to reduce mortality, though recurrent stroke risk in athletes with AF mirrors that of non-athletes, despite an elevated AF incidence. Management of AF in athletes is complex, with limited evidence guiding anti-thrombotic strategies. In this setting, specific recommendations are sparse, particularly in sports where bleeding risk is heightened. Individualized management, emphasizing shared decision-making, is critical to balance stroke prevention with athletic performance. Rhythm control strategies, such as catheter ablation, may be a reasonable first-line treatment option for athletes, particularly in those desiring to avoid long-term medication. This review synthesizes the current literature on the incidence, predictors, and management of stroke in athletes with AF.